2016
DOI: 10.1002/jcb.25621
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the 3D Phenotype Upon Dispersal of Cultured Cell Spheroids Into Monolayer Cultures

Abstract: In functional cytometric studies, cultured cells are exposed to effectors (e.g., drugs), and the heterogeneity of cell responses are studied using cytometry techniques (e.g., image cytometry). Such studies are difficult to perform on 3D cell cultures. A solution is to disperse 3D clusters and transfer the cells to the 2D state before applying effectors and using cytometry. This approach requires that the lifetime of the 3D phenotype be longer than the duration of the experiment. Here we studied the dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…[2,6] For this purpose, the performance of a number of drugs has been analyzed using 2D in vitro models due to their simplicity, reproducibility, and lowcost. [7][8][9][10][11] Still, these 2D in vitro models can only be used to investigate the direct effects of the drugs in the cells and do not take into consideration the role of the physiological 3D environment of the cells in drugs resistance. Therefore, the exclusive use of 2D in vitro models can lead to poor predictive results concerning drug's effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2,6] For this purpose, the performance of a number of drugs has been analyzed using 2D in vitro models due to their simplicity, reproducibility, and lowcost. [7][8][9][10][11] Still, these 2D in vitro models can only be used to investigate the direct effects of the drugs in the cells and do not take into consideration the role of the physiological 3D environment of the cells in drugs resistance. Therefore, the exclusive use of 2D in vitro models can lead to poor predictive results concerning drug's effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25,27] On the other hand, researchers are developing drug resistant 2D cell cultures. [7,[33][34][35][36][37][38][39][40] These models show a drug resistance profile more alike to that found in in vivo tumors and can be analyzed through standardized assays and equipment used for conventional 2D cell cultures. Recently, Koshkin et al demonstrated that 3Dderived MCF-7 cells (cells obtained from 3D spheroids disaggregation) are able to preserve their 3D-phenotype when cultured in 2D.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since SCs and CSCs have the unique in vitro capacities to survive and proliferate in an anchorage‐independent manner and generate mammospheres (MMs) in suspension culture conditions [Dontu et al, ; Medina et al, ], we and others have utilized the property of MM formation to culture SCs/CSCs ex situ. Additionally, as SCs are characterized by a low rate of cell proliferation ex situ, SCs can be enriched during MM formation by their capacity to retain higher levels of a membrane‐labeling dye compared to the progeny cells generated from the SCs [Dontu et al, ; Zucchi et al, , ; Pece et al, ; Tosoni et al, ; Piscitelli et al, ; Koshkin et al, ].…”
mentioning
confidence: 99%